Sperm quality in male Barbus barbus L. fed different diets during the spawning season - Alavi, Sayyed Mohammad Hadi; Psenicka, Martin; Policar, Tomás; Rodina, Marek; Hamácková, Jitka; Kozák, Pavel; Linhart, Otomar (Fish physiology and biochemistry, 2009)
Sperm quality of Barbus barbus L. was compared among the three following dietary regimes: Group A, fed 100% commercial diet (Karpico containing 33% crude protein and 6% fat), Group B, fed 78% commercial diet and 22% frozen chironomid (Chironomus plumosus) larvae, and Group C, fed 56% commercial diet and 44% frozen chironomid larvae. Concentrations of polyunsaturated fatty acids (PUFAs) in Group A, B, and C were 39.1, 42.0, and 44.6, respectively, as a percentage of total fatty acids. Sperm morphology, volume, concentration and motility, total number of spermatozoa, and osmolality of the seminal plasma were compared during the spawning season. Dietary regime did not influence sperm volume, concentration, or total number of spermatozoa, osmolality of seminal plasma, or the percentage of motile sperm, but significantly affected sperm morphology (except for anterior and posterior parts of the midpiece) and sperm velocity (P < 0.05). Groups B and C showed similar sperm characteristics during the spawning season compared to Group A. Almost all parameters changed either among or within groups during the spawning season, suggesting differences in terms of the optimal time for sperm collection. The best time for sperm collection was March for Group A, but April for Groups B and C, when the osmolality of the seminal plasma measured 289 mOsmol kg(-1) and sperm motility was maximal. Spermatogenesis, hydration, and cell decomposition were confirmed as the three major parameters controlling sperm characteristics during the spawning season. The possible correlation between sperm morphology and motility requires further study.
Keywords: Animal Nutritional Physiological Phenomena; fyziologie výživy zvířat; Male; Sperm Motility; vodní hospodářství; spermatogeneze; Spermatozoa; Spermatogenesis; mužské pohlaví; Cyprinidae; dieta; osmolární koncentrace; sperma; Semen; Animals; roční období; Seasons; zvířata; Aquaculture; Osmolar Concentration; motilita spermií; spermie; Diet